2018
DOI: 10.1113/jp276894
|View full text |Cite
|
Sign up to set email alerts
|

Inducible nitric oxide synthase‐derived nitric oxide reduces vagal satiety signalling in obese mice

Abstract: Key points Obesity is associated with disrupted satiety regulation. Mice with diet‐induced obesity have reduced vagal afferent neuronal excitability and a decreased afferent response to satiety signals. A low grade inflammation occurs in obesity with increased expression of inducible nitric oxide synthase (iNOS). Inhibition of iNOS in diet‐induced obese mice restored vagal afferent neuronal excitability, increased the afferent response to satiety mediators and distention of the gut, and reduced short‐term ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…The study by Yu et al . () indicates a role for nitric oxide in the hyperphagia observed in high fat diet conditions and highlights the need for improved understanding of the dynamic role nitric oxide plays in modulating gastrointestinal vagal afferent signalling and the subcellular signalling pathways involved. This will ultimately lead to new peripheral targets for the pharmacotherapy of obesity.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…The study by Yu et al . () indicates a role for nitric oxide in the hyperphagia observed in high fat diet conditions and highlights the need for improved understanding of the dynamic role nitric oxide plays in modulating gastrointestinal vagal afferent signalling and the subcellular signalling pathways involved. This will ultimately lead to new peripheral targets for the pharmacotherapy of obesity.…”
mentioning
confidence: 98%
“…Yu et al . () have taken these observations further and demonstrated that the dampened mechanosensitivity and chemosensitivity, observed in high fat diet‐induced obese mice, is reversed by addition of an iNOS inhibitor at least in subgroups of jejunal vagal afferent fibres. Further, they demonstrated that daily i.p.…”
mentioning
confidence: 98%
See 3 more Smart Citations